2012
DOI: 10.1186/2047-217x-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell sequencing analysis characterizes common and cell-lineage-specific mutations in a muscle-invasive bladder cancer

Abstract: BackgroundCancers arise through an evolutionary process in which cell populations are subjected to selection; however, to date, the process of bladder cancer, which is one of the most common cancers in the world, remains unknown at a single-cell level.ResultsWe carried out single-cell exome sequencing of 66 individual tumor cells from a muscle-invasive bladder transitional cell carcinoma (TCC). Analyses of the somatic mutant allele frequency spectrum and clonal structure revealed that the tumor cells were deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 36 publications
3
102
1
1
Order By: Relevance
“…The six somatic mutations that were discovered in the present study were single base changes, and none of them had previously been identified in the TCC genome. The novel nonsynonymous mutation genes that were detected did not include the well-known bladder cancer genes (FGFR3, RAS, TP53 and RB1) and contrasted with the findings of previous studies (14)(15)(16). This discrepancy may be due to differing experimental conditions, and algorithm and filter use.…”
Section: Discussioncontrasting
confidence: 56%
“…The six somatic mutations that were discovered in the present study were single base changes, and none of them had previously been identified in the TCC genome. The novel nonsynonymous mutation genes that were detected did not include the well-known bladder cancer genes (FGFR3, RAS, TP53 and RB1) and contrasted with the findings of previous studies (14)(15)(16). This discrepancy may be due to differing experimental conditions, and algorithm and filter use.…”
Section: Discussioncontrasting
confidence: 56%
“…In recent years, a large number of studies have been reported using single cell analysis to analyze individual tumor cells isolated from breast cancer (Navin et al, 2011; Deng et al, 2014; Wang et al, 2014; Eirew et al, 2015), colon cancer (Zong et al, 2012; Yu et al, 2014), pancreatic adenocarcinomas (Ruiz et al, 2011), muscle-invasive bladder cancer (Li et al, 2012b), intestinal cancer (Grün et al, 2015), lung adenocarcinoma cancer (Kim et al, 2015), renal cell carcinoma (Gerlinger et al, 2012; Li et al, 2012b), and acute myeloid leukemia (Ding et al, 2012; Hughes et al, 2014; Paguirigan et al, 2015). For example, Navin and colleagues investigated copy number variation in single tumor cells using DOP WGA followed by DNA sequencing to determine cell population structure and tumor evolution patterns in a single breast tumor (Navin et al, 2011).…”
Section: Application Of Single Cell Analysismentioning
confidence: 99%
“…Analyses of the somatic mutant allele frequency spectrum and clonal structure revealed that the tumor cells were derived from a single ancestral cell, but that subsequent evolution occurred, leading to two distinct tumor cell subpopulations which provide evidence for the monoclonal origin of TCC [26]. …”
Section: Generation Model Of Tumor Heterogeneitymentioning
confidence: 99%